Deteksi Kerusakan DNA Spermatozoa Semen Segar dan Semen Beku Sapi Menggunakan Pewarnaan Toluidine Blue (DETECTION OF SPERM DNA DAMAGE INFRESH AND FROZEN SEMEN USING TOLUIDINE BLUE STAINING) - Priyanto, Langgeng; Arifiantini, Raden Iis; Yusuf, Tuty Laswardi (Jurnal Veteriner, 2015)
Sperm DNA integrity is very important in the success of fertilization and embryo development.Toluidine blue (TB) is a sensitive staining to examine the chromatin structure of sperm. The aim of thisstudy was to detect the sperm DNA damage before and after freezing using TB. Semen was obtained fromeight superior bulls (two Brahman, two Ongole, two Simental and two Limosin) belong to Lembang ArtificialInsemination Centre. Semen was collected twice a week using artificial vagina, then was evaluatedmacrocopically and microscopically after collected, including sperm motility, viability, plasma membraneintegrity (MI) and acrosome intact (AI), sperm concentration, abnormality and sperm DNA integrity. Thesemen that been used in this study showed the total motility was more than 70%, sperm concentrationwas more than 1000x106, and the sperm abnormality was below 20%. The result showed that the qualityof semen after freezing processed was decreased significantly (P<0.05) on percentage of sperm motility,viability, MI and AI, whereas there was no different on DNA integrity (P>0.05). Sperm DNA integrity offresh and frozen semen were 93.91±4.77% and 92.06 ±2.41% respectively. The decrease of DNA integritywas low (1.84%) compared to motility (28.3%), viability (21.6%), MI (14.1%), and AI (11.8%). In conclusion,toluidine blue can be used to detect of DNA damage and the freezing process will not decrease the DNAintegrity.
Keywords: DNA damage, toluidine blue, bull sperm